Perencanaan Strategi SI/TI Menggunakan Metode Ward and Peppard : Studi Kasus Cafe Ungu - Arisanti Dwi Safitri; Sekar Ajeng Ramadhani; Salsa Fathaturrahma; Anastasya Yuniar; Widiyana Mustofiyah; Ito Setiawan (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
This research aims to develop strategies for SI/TI Cafe Ungu to improve operational efficiency and competitiveness. Cafe Ungu is still struggling to integrate technology, so some business processes are still done manually and are less efficient. The method used to analyze the internal and external conditions of the company, as well as the SI/TI conditions, is Ward and Peppard with a qualitative approach through interviews and observations. SWOT Analysis, Value Chain, PEST, and McFarlan Strategic Grid are components of the method used to determine the appropriate application for Cafe Ungu. The analysis results show that automated bookkeeping, web-based inventory management, and centralized POS systems can improve data accuracy and operational efficiency. Additionally, it is recommended that the customer experience be improved with a digital queue system and modern payment methods. By implementing this strategy, Cafe Ungu is expected to adapt to market changes and enhance its competitiveness. Thus, the SI/IT strategy based on the Ward and Peppard method successfully supports Cafe Ungu's long-term goals.